International Coordination of Macroeconomic Policies in Face of Financial Crisis and Global Imbalances - Bogołębska, Joanna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Increased interest in coordination of macroeconomic policies, which is due to both the instability of the global economy as the consequence of financial crisis and the phenomenon of global imbalances, has been observed during last years. The main arguments for coordinated actions are: negative spillover effects of monetary policy implemented unilateral in globalized and integrated global economy, especially in times of economic downturns and difficulties in adoption of adjustment policies unilaterally. However, both the uncertainty about the effects and difficulties with implementation are the main brakes for coordinated actions. Both theoretical and empirical studies on international coordination of macroeconomic policies stress that the significance of it falls in times of stability and economic booms.